Investigation of the Effectiveness of Time Perspective Education in Reducing Risky Behaviors (Case Study: Self-Referred Addicts at Treatment Centers in Isfahan) - Pilehvar Zavareh, Somayeh; Hamidian, Akram (Mental Health and Lifestyle Journal, 2026)
This study was conducted to investigate the effectiveness of time perspective education in reducing risky behaviors among self-referred addicts. The research employed a quasi-experimental design (pre-test–post-test with control group), with the statistical population comprising all self-referred addicts at the medium-term treatment and residential centers of Shohada Khapushan in Isfahan during 2019. A sample of 30 participants was selected via convenience sampling from volunteers and randomly assigned to experimental and control groups. Data were collected using the Centers for Disease Control and Prevention (CDC) Risky Behaviors Questionnaire. Time perspective education was delivered over eight 2-hour sessions based on Norouzi’s (2016) guidelines. Data analysis using ANCOVA test indicated that time perspective education significantly reduced risky behaviors among self-referred addicts by 67.0% (p < .01). Additionally, it reduced violence and law-breaking by 35% (p < .01), alcohol consumption by 35% (p < .05), risky driving by 27% (p < .01), risky sexual relationships by 30% (p < .01), and poor nutrition and insufficient physical activity by 35% (p < .01). Therefore, time perspective education can reduce risky behaviors in drug addicted people.